(untitled) (KULT_online, 2009)
As athletics is to competitive sports, so is biography to historical research: quite simply, the pinnacle. It is therefore fitting that historian Frank Becker has most recently dedicated himself to both. All told, Becker’s is a multi-faceted work which examines Diem’s personal and career evolution in conjunction with the dominant mentality of the times, which extend from the 19th century to the post-war era. The first volume released (chronologically, volume three of four) is devoted to the Nazi era and, above all, Carl Diem’s stance on the regime.